Reviews of Environmental Contamination and Toxicology Volume 208 Perfluorinated alkylated substances - De Voogt, Pim.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Atmospheric Perfluorinated Acid Precursors: Chemistry, Occurrence and Impacts by Cora J. Young and Scott A. Mabury.- Isomer Profiling of Perfluorinated Substances as a Tool for Source Tracking: A Review of Early Findings and Future Applications by Jonathan P. Benskin, Amila O. De Silva, and Jonathan W. Martin.- Biodegradation of Fluorinated Alkyl Substances by Tobias Frömel and Thomas P. Knepper.- Perfluorinated Substances in Human Food and Other Sources of Human Exposure by Wendy D Hollander, Pim de Voogt, Wim De Coena, and Lieven Bervoetsa.- Index.
Atmospheric Perfluorinated Acid Precursors: Chemistry, Occurrence, and Impacts -- Isomer Profiling of Perfluorinated Substances as a Tool for Source Tracking: A Review of Early Findings and Future Applications -- Biodegradation of Fluorinated Alkyl Substances -- Perfluorinated Substances in Human Food and Other Sources of Human Exposure.
Keywords: Environmental sciences; Environmental management; Environmental toxicology; Environment; Environmental Management; Ecotoxicology